On the nymphs of lantana lace bug Teleonemia scrupulosa Stål (Hemiptera: Heteroptera: Tingidae: Tinginae): ontogenetic features of integumentary structures highlighted - Guidoti, Marcus; Barcellos, Aline (Zootaxa, 2013)
The five instars of Teleonemia scrupulosa Stål are described. The postembryonic ontogenetic development of integumen-tary structures is emphasized, with a discussion on its potential use in cladistic studies within Tingidae.